2018
DOI: 10.4103/ccd.ccd_70_18
|View full text |Cite
|
Sign up to set email alerts
|

Candida species diversity in oral cavity of type 2 diabetic patients and their In vitro antifungal susceptibility

Abstract: Objective:To identify and compare the species variation and Colony Forming Units of the species and antifungal susceptibility from oral rinse samples of individuals in poorly-controlled, moderately-controlled and well controlled diabetes patients with control group.Subjects and Methods:Study group comprised of well-controlled, moderately-controlled and poorly controlled Type II diabetic patients grouped according to the level of glycated hemoglobin concentration with 50 patients in each group and 50 healthy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Oral candidiasis is a common fungal infection in type 2 diabetics that presents as discrete and confluent white plaques on the buccal mucosa, tongue, and sometimes the palate, gingivae, and floor of the mouth; these plaques may be wipeable. 9 Many studies have reported that Candida species are the most common yeast isolated from diabetic foot ulcers. However, few studies have reported C. albicans as the most common species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral candidiasis is a common fungal infection in type 2 diabetics that presents as discrete and confluent white plaques on the buccal mucosa, tongue, and sometimes the palate, gingivae, and floor of the mouth; these plaques may be wipeable. 9 Many studies have reported that Candida species are the most common yeast isolated from diabetic foot ulcers. However, few studies have reported C. albicans as the most common species.…”
Section: Discussionmentioning
confidence: 99%
“…Bhuyan, L et al (2018) 9 showed a higher proportion of strains different from C. albicans species isolated from unstimulated saliva and their variable susceptibility to the commonly prescribed antifungals in diabetes indicate the necessity of the special mode of diagnostic and therapeutic management. This highlights the importance of routine candidal speciation and appropriate selection of prophylactic antifungal regimen after susceptibility testing, especially during intermittent visits.…”
Section: Indiamentioning
confidence: 99%
“…Bhuyan and Hassan[ 8 ] reported that a comparatively low number of non-albicans were seen in healthy individuals. Candida albicans showed increased resistance to fluconazole in patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…to voriconazole and amphotericin B [ 31 ]. Reduced susceptibility to antifungals in diabetic patients has also been demonstrated in the clinical setting [ 32 , 33 , 34 ]. Bhuyan et al [ 32 ] observed a significant difference in the number of C. albicans and C. parapsilosis that is resistant to fluconazole in diabetes patients compared to healthy controls.…”
Section: Challenges In the Treatment Of Candida mentioning
confidence: 99%